2019
DOI: 10.1021/acs.analchem.9b01001
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots Wrapped Gold Nanoparticles with Integrated Enhancement Mechanisms as Sensitive and Homogeneous Substrates for Surface-Enhanced Raman Spectroscopy

Abstract: Rational engineering of highly stable and Ramanactive nanostructured substrates is still urgently in demand for achieving sensitive and reliable surface-enhanced Raman spectroscopy (SERS) analysis in solution phase. Herein, monodisperse Ndoping graphene quantum dots wrapped Au nanoparticles (Au-NGQD NPs) were facilely prepared, and further their applications as substrates in SERS-based detection and cellular imaging have been explored. The as-prepared Au-NGQD NPs exhibit superior long-term stability and biocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Surface-enhanced Raman spectroscopy (SERS) has been intensely studied in the last four decades in analytical chemistry and food safety ( Nguyen et al, 2014 ). The application of SERS in myriad applications is driven by its fingerprinting specificity, multiplexing potential, single-molecule level sensitivity, bioimaging, and bioanalysis capabilities ( Miao et al, 2019 ). SERS is the scientific art of the amplification of a traditional low Raman signal using coinage of roughened metal surface ( Ling et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-enhanced Raman spectroscopy (SERS) has been intensely studied in the last four decades in analytical chemistry and food safety ( Nguyen et al, 2014 ). The application of SERS in myriad applications is driven by its fingerprinting specificity, multiplexing potential, single-molecule level sensitivity, bioimaging, and bioanalysis capabilities ( Miao et al, 2019 ). SERS is the scientific art of the amplification of a traditional low Raman signal using coinage of roughened metal surface ( Ling et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SERS substrate, as the impetus for this phenomenon, has been explored to a great extent, and conventional roughened metallic nanoparticles (NPs), such as Au, Ag, and Cu, are the cornerstones in SERS applications. Typical noble metal-based SERS substrate entails deposition of the metals on some support, and for the longest time, the support has been solid glass/silicon wafer ( Nguyen et al, 2014 ; Miao et al, 2019 ). The NPs have been favorable substrates due to their compatible size and richness in localized surface plasmon resonance (LSPR) properties ( Miao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the tiny size of NGQDs leads to their accumulation, which decreases the photochemical response in the PEC reaction process. In addition, their slow electron conductivity also limits the performance of NGQDs in PEC detection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The photocurrent intensity of NGQD-ZnNb 2 O 6 /g-C 3 N 4 was much higher than for ZnNb 2 O 6 and g-C 3 N 4 , which was mainly due to the efficient charge separation and enhanced photocatalytic activity of the Zn/7CN catalyst [ 17 ]. Zhu prepared gold–nitrogen-doped graphene quantum dot (Au/NGQD) nanoparticles (NPs) and studied their integrated enhancement mechanisms, finding the potential of Au/NGQD NPs to be superior to Surface Enhanced Raman Scattering (SERS) substrates for on-site Raman detection, owing to their electromagnetic and chemical enhancement [ 16 ]. You developed a sensitive electrochemiluminescence (ECL) aptasensor for zearalenone detection based on NH 2 -Ru@SiO 2 NPs, showing a wide linear range of 10 fg mL −1 to 10 ng mL −1 and a low detection limit of 1 fg mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…GQDs possess stacked graphene-like sp 2 carbon-type layer structures inside the dots, endowing them with some of the unusual properties of graphene such as unique edge effects and quantum confinement, leading to broadband optical absorption [24,25]. GQDs have attracted increasing interest in many fields, such as electrochemical biosensors, photoelectrochemical biosensors, drug delivery, bioimaging, and energy conversion [26][27][28][29]. Furthermore, both theoretical and experimental results have indicated that the introduction of nitrogen atoms into the carbon lattice of quantum dots (NGQDs) would tailor the electronic property and chemical reactivity of GQDs [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%